INFLUENCE OF TEMPERATURE ON RADIATION-INDUCED GRAIN BOUNDARY SEGREGATION IN TERNARY Fe-Cr-Ni ALLOYS - Karpikov, A.N.; Kislitsin, S.B.; Nesterova, A.Yu. (Recent Contributions to Physics, 2018)
The model for calculation radiation-induced grain boundary segregation in the ternary alloys, caused by fluxes of vacancies and interstitials from volume of grain to boundary is presented. Influence of temperature is expressed in acceleration diffusion processes with its growth. Maximum effect of segregation is shown at temperatures 900 K. The received results will well be coordinated to available experimental data.